Patients’ and Professionals’ Views on Managing Fibromyalgia - Erica Briones-Vozmediano; Carmen Vives-Cases; Elena Ronda-Pérez; Diana Gil-González (Pain Research and Management)
BACKGROUND: Managing fibromyalgia is a challenge for both health care systems and the professionals caring for these patients, due, in part, to the fact that the etiology of this disease is unknown, its symptoms are not specific and there is no standardized treatment.